Contemporary Strategies and Outcomes of Dedicated Chronic Total Occlusion Percutaneous Coronary Intervention Programs: A Prospective Multicentre Registry. (7th December 2021) - Vanhaverbeke, Maarten; Eertmans, Ward; Holvoet, Wouter; Hendrickx, Ief; McCutcheon, Keir; Dubois, Christophe; Dens, Joseph; Bennett, Johan
Abstract : Background . The field of CTO PCI is expanding, but successful and safe percutaneous coronary intervention (PCI) of coronary chronic total occlusions (CTO) requires a substantial resource and experience investment. We aimed to assess temporal trends in strategies and outcomes of 2 dedicated programs for CTO PCI. Methods . Between 2011 and 2020, 920 CTO PCI procedures were prospectively included at 2 referral centres in Belgium. Temporal trends were assessed, and logistic regression models were built to identify predictors of outcome. Results . Despite an increase in lesion complexity (the J-CTO score increased from 1.3 in year 1 to 1.7–2.0 in years 8-9, p < 0.001 ), technical success improved from 70.0% to 85.6% in year 9 ( p value for trend <0.001). We observed the most significant improvement starting at years 3-4 (OR 2.3 in year 4 versus year 1, p = 0.018 ). Together with an increase in success rates and lesions complexity, there was an increase in the use of dual injections, retrograde approaches, the number of balloons and stents, and the use of microcatheters. Conversely, there was a decrease in large bore access, an increase in radial approach, and a shift towards contemporary dissection/reentry techniques. This strategy resulted in a stable major complication rate of 4.7% ( p value for trend 0.33). The rate of coronary procedure-related myocardial injury was high (71.0%) and was associated with the use of more intracoronary devices. Conclusions . Three to four years after initiation of a dedicated CTO PCI program with 50 CTO PCIs per year, consistent high technical success and low complication rates are achieved using contemporary strategies.